Effectiveness of non-pharmacological methods in reducing pain in pediatric patients and the role of nursing. Systematic review - Pérez-Pozuelo, Juan Manuel; Hernández-Iglesias, Sonsoles; Pereira-Afonso, Mónica Raquel; Checa-Peñalver, Abel; García-Valdivieso, Inmaculada; López-González, Ángel; Gómez-Cantarino, Sagrario (Frontiers in Pediatrics, 2026)
IntroductionThe prevalence of pediatric pain has increased and is a leading cause of hospital attendance. Non-pharmacological treatments for pain relief in pediatrics are experiencing a boom.MethodologySystematic review, following the quality guidelines of the PRISMA 2020 declaration. Previously determined inclusion and exclusion criteria were followed for the selection of studies.ResultsThe use of the vibrating and cold bee combined with a distractor is the most useful method, with virtual reality being the ideal distractor for the palliation of pediatric pain. The role of the nurse is essential to detect pain, choose the analgesia method and administer it.DiscussionThe non-pharmacological techniques proposed and studied according to the selection of articles are useful in the reduction of pediatric pain according to the scales used in each study.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025640378, identifier CRD42025640378.